ANALISIS ETIKA TEOLOGIS KRISTEN TERHADAP FENOMENA ETNOSENTRISME DAN EKSKLUSIVISME SUKU DI LINGKUNGAN GEREJA - Ajeng Kartin Paramma’; Alber; Marisa Konda; Afriani Palangiran (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2026)
This study examines the phenomena of ethnocentrism and ethnic exclusivism within church communities from the perspective of Christian theological ethics. Many churches in Indonesia, particularly those with ethnic bases, tend to over-maintain ethnic identity, which gradually shifts into closed attitudes toward other groups. This research employs a qualitative library research method with a descriptive-analytical approach. The findings indicate that ethnocentrism and ethnic exclusivism within church communities contradict the principles of Christian theological ethics, particularly the doctrine of Imago Dei and the church's calling as an inclusive community of God's Kingdom. The church is called to transcend ethnic boundaries by building equal, open, and universally loving relationships as taught by Christ.